Emmanuel Maignan e Francesco Borromini. Il progetto di una villa scientifica nella Roma barocca Lettera Ventidue, Siracusa 2020 (diségno, 2020)
This beautiful book by Alessio Bortot on the project, imagined but never realized, of a ‘scientific villa’ in baroque Rome is a fascinating example of the ‘circumstantial power’ of Drawing, when it is a document, and of the irresistible ‘power of figuration’ and ‘morphogenesis’ that it assumes when configured as an investigative process that, through the structures of geometric thought, generates and induces the design gesture (read more).